PREVENSI DAN PROTEKSI KASUS BUNUH DIRI BERBASIS SEKOLAH - Lisya Chairani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
This article discusses how suicide case can be prevented by the school based prevention and protection. Child has a special risk in suicide done by parent. Maybe the innoncent child will be brought together by parent for his/her suicide or the child will accept directly or nor the psychological impact of that case.Therefore, the suicide can be said as one the hardness to child, whether child as a victim, witness and or as the person who leaved by the parent with million questions in his/her mind. There are many factors cause one does the suicide.They are psychological, biological, and family environment. The prevention of suicide can be done by school based prevention and protection.This activity of course envoles the competence person in its area. The school has to foms the net working to be able to referl the student who has certain problem in order not to does suicide.